Developing Professional-Pedagogical Competence in Future Teachers of Visual Arts - Kadirova Shakhnoza Aminbaevna (Zien Journals, 2023)
Purpose of the study is to identify, theoretically substantiate, and experimentally test the pedagogical conditions for developing professional-pedagogical competence in future teachers of visual arts based on a polyartistic approach
Keywords: polyartistic; pedagogical; teachers; approach